ТАЪЛИМ ТАРАҚҚИЁТИ ҲАМИША ДОЛЗАРБ: ТАЪЛИМ ОЛИШ ҲАММА УЧУН ОЧИҚ - Елмуратова, А.; Алламбергенова, Б. (SCIENCE and SOCIETY, 2020)
This article highlights the views on the renewed “Law on Education”, on new forms of education, specifically highlights the importance of inclusive education, its reflection in the new law.
Keywords: education service; form of education; person; distance; part-time; evening; inclusive; necessity; law; needs